FAKTOR-FAKTOR YANG MEMPENGARUHI IBU MEMBERIKAN MAKANAN TAMBAHAN PADA BAYI 0-6 BULAN DI DESA NAMO PINANG KECAMATAN NAMO RAMBE KABUPATEN DELI SERDANG TAHUN 2020 - Kristin Natalia; Vitrilina Hutabarat; Stefani Anastasia Sitepu (JURNAL ILMIAH DHDT - KEBIDANAN, 2020)
Supplementary feeding is an effort to provide additional food and to increase nutritional intake to meet nutritional needs in order to achieve a good nutritional status. Food plays an important role in the growth and development of children, because the growing child needs are different from adults. The purpose of this study is to find out the knowledge of mothers about supplementary food in infants 0-6 months. This research is a descriptive design with a sample of 20 mothers in Namo Pinang village, taking a sample using total sampling. Data analysis using the computer program SPSS with the chi-square test. Statistical test results obtained p value = 0.001 which means p <0.005, thus it can be concluded that it has the most dominant influence on supplementary feeding in infants 0-6 months.